Microbiological characterization of land set-aside before and after Roundup desiccation - M. Růžková; L. Růžek; K. Voříšek; P. Vráblík; D. Musilová (Plant, Soil and Environment, 2011)
Luvic chernozem (set-aside from 1996) was evaluated. The first period, before Roundup desiccation (2002-2003), was characterized by black, spontaneous and controlled fallows (mowed with the removal of plant biomass or mulched); the following period (2003-2004) by black fallow with repeated Roundup applications; and the last period (2004-2006) involved re-grassing by a mowed Lolium multiflorum Lam. monoculture. The characterization included microbial biomass, available organic carbon, basal respiration, metabolic quotient, biomass-specific available organic carbon, arylsulfatase activity, soil organic matter carbon and total nitrogen. Mulching of pure cultures of grasses and legumes contributed to a high soil organic matter accumulation. Repeated Roundup desiccation caused a strong (highly significant) decrease of arylsulfatase activity (-28%), however highly significant increase of microbial biomass (+69%) and nitrate-nitrogen (+86%) were determined. The subsequent re-grassing compensated the changes described. The soil biological properties were best preserved on mulched fallow with Lotus corniculatus L. and Festuca pratensis L., also in regard to contamination with weeds.